German economics: Its current form and content - Janina Urban; Florian Rommel (Cusanus Hochschule für Gesellschaftsgestaltung, Institute für Ökonomie und für Philosophie, 2020)
This paper provides a systematic assessment of academic economics teaching, research and policy advice in Germany. It assembles recent empirical studies and contributes by presenting their main findings in a comprehensible manner as well as contextualizing them in the current economic and methodological discourses. As most studies are only available in German this paper also contributes by making these findings accessible to the international debate on the special characteristics of economics as a discipline.
Keywords: A11; A14; A22; A23; B41; 330; Economics Education; Economics Research; Pluralism; Mainstream Pluralism; German Economics